Efficacy of sodium hypochlorite against multidrug-resistant Gram-negative bacteria. Issue 3 (November 2018) - Köhler, A.T.; Rodloff, A.C.; Labahn, M.; Reinhardt, M.; Truyen, U.; Speck, S.
Summary: Background: Increased antimicrobial resistance has been observed among many bacteria leading to treatment failures in human and veterinary medicine. Disinfection is a prerequisite for infection control and prevention in healthcare settings. Chlorine compounds are cost-effective and accessible worldwide. Aim: To determine the efficacy of sodium hypochlorite (NaOCl) against multidrug-resistant Gram-negative bacteria (MDR-GNB). Methods: Minimum inhibitory concentrations (MICs) were determined using broth macro-dilution. Bactericidal efficacy was measured by qualitative and quantitative suspension tests followed by practical tests without mechanical action on stainless steel carriers. The guidelines of the German Association for Applied Hygiene were followed. Findings: Results varied remarkably depending on the method. MICs were 0.1% or 0.2% NaOCl. Qualitative suspension tests revealed up to 500-fold lower bactericidal concentrations. Pseudomonas aeruginosa ( P = 0.0025) was significantly less susceptible in these tests whereas quantitative suspension tests revealed no significant differences between strains ( P > 0.05). Practical tests determined bactericidal concentrations of 0.8–0.32% NaOCl at 1 min of contact and even lower concentrations for longer contact times. At 1 min, five Klebsiella were significantly less susceptible ( P = 0.0124), whereas the lower susceptibility of P. aeruginosa was not confirmed. Organic load inhibited bactericidal activity significantly, whereas contact time had a marginal effect. Differing test results underline that MIC determination and qualitative suspension tests may be insufficient approaches to evaluate bacterial susceptibility or resistance. Conclusion: NaOCl efficiently reduced Pseudomonas aeruginosa, Acinetobacter spp., and Klebsiella spp., most notably in the absence of organic matter. Strain- and species-specific differences in susceptibility were noticed, but in general MDR-GNB revealed no higher tolerance to NaOCl.